Investigation on Coherencies between Residual Stresses and Tool Geometry by Hard Turning (Hungarian Journal of Industry and Chemistry, 2011)
A wide group of scientists are concerned by the studying of chip removal in hard turning even today. The reason for that is that the cutting conditions must be chosen accurately to exploit the benefits provided by hard turning. Among the parameters influencing the material removal, the edge geometry of the cutting tool also plays a decisive role since the effective chip removal is ensured by a special edge formation made from a hardened surface of about 60 HRC hardness. In this paper the effect of the tool rake angle on the chip removal process is investigated, examining a relatively wide interval of the rake angle value.